Australian healthcare workers experiences of peer support during COVID-19: Hand-n-Hand peer support. (December 2022) - Musgrove, Erica; Bil, Daniel; Bridson, Tahnee; McDermott, Brett
Introduction: Founded at the beginning of the COVID-19 pandemic, Hand-n-Hand Peer Support (HnH) offers free, confidential peer support to healthcare workers (HCWs) across Australia and New Zealand. This survey aimed to evaluate HCWs experiences of peer support and collect demographic data about what groups of HCWs were seeking support. Methods: An online survey was conducted in November 2021 of HCWs who were either active or past HnH participants ( n = 158). Questions included 5-point Likert scales, multiple choice and free text responses. Results: We received 66 responses (42% response rate). The median age range of respondents was 41–45 years and most were female (87.9%). Most respondents (57.4%) reported experiencing no barriers to accessing peer support. The vast majority (81.4%) of HCWs reported a 'good' or 'very good' peer support experience. Respondents felt peer support helped in multiple ways, particularly in feeling less alone and having a safe space to discuss issues. Conclusion: Australian HCWs accessing peer support tended to be female and more senior clinicians. Most HCWs engaged in HnH reported overall very positive experiences. Our survey helped to identify several areas for improvement in HnH, including clearer marketing about peer support and more targeted triage assessments.